2017
DOI: 10.1016/j.ajur.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Testicular torsion in undescended testis: A persistent challenge

Abstract: ObjectiveTo evaluate the management and outcomes of patients who presented with torsion of an undescended testis and review the reported series in the literature.MethodsThe case records of 13 patients operated for testicular torsion involving undescended testis were retrospectively reviewed. The medical records included age at presentation, medical history, physical examination, operative findings and the results of follow-up. The diagnosis of torsion of undescended testis was made clinically and confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 26 publications
4
59
0
3
Order By: Relevance
“…11 Naouar et al in 2015 also reported 13 cases of testicular torsion where 9 cases reported between 6-48 hours, reflecting a delayed presentation. 8 In present report also, the patient reported after 48 hours of symptoms. It might be due to nonspecific symptoms, lack of awareness and a poor availability of health services particularly in rural regions of developing nations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…11 Naouar et al in 2015 also reported 13 cases of testicular torsion where 9 cases reported between 6-48 hours, reflecting a delayed presentation. 8 In present report also, the patient reported after 48 hours of symptoms. It might be due to nonspecific symptoms, lack of awareness and a poor availability of health services particularly in rural regions of developing nations.…”
Section: Discussionsupporting
confidence: 70%
“…Risk of torsion in UDT is reported to be 10 times higher compared with a normal descended testis. 8 Johnson also reported torsion in 21% cases of UDT in his study of an inguinal cryptorchidism 9 but cases of torsed IAT are only available as case reports. So, an exact risk of torsion in an IAT couldn't be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Except for 5 cases of emergency orchidectomy, only 1 of 6 cases with testicular descent fixed had long-term testicular survival (up to 21 years) and developed well. Naouar et al [17] retrospectively analyzed 12 children with testicular torsion involving UDT; only 1 case (1-year old) with torsion degree of 180° obtained normal-sized testes in long-term 3-year follow-up. Pogorelić et al [4] reported that 3 out of 8 cases of cryptorchidism were rescued and they were all over 13 years of age, and within 6 h from the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Undescended testis is one of the most common paediatric condition for which surgery is performed 3. It affects 3% of all term babies and up to half of all preterm babies 3.…”
Section: Introductionmentioning
confidence: 99%
“…It affects 3% of all term babies and up to half of all preterm babies 3. Intra-abdominal torsion has been clinically described in older children and has varied clinical presentations leading to delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%